Early life environmental and pharmacological stressors result in persistent dysregulations of the serotonergic system - Wong, Peiyan; Sze, Ying; Gray, Laura Jane; Chang, Cecilia Chin Roei; Cai, Shiwei; Zhang, Xiaodong (Frontiers in Behavioral Neuroscience, 2015)
Dysregulations in the brain serotonergic system and exposure to environmental stressors have been implicated in the development of major depressive disorder. Here, we investigate the interactions between the stress and serotonergic systems by characterizing the behavioral and biochemical effects of chronic stress applied during early-life or adulthood in wild type (WT) mice and mice with deficient tryptophan hydroxylase 2 (TPH2) function. We showed that chronic mild stress applied in adulthood did not affect the behaviors and serotonin levels of WT and TPH2 knock-in (KI) mice. Whereas, maternal separation (MS) stress increased anxiety- and depressive-like behaviors of WT mice, with no detectable behavioral changes in TPH2 KI mice. Biochemically, we found that MS WT mice had reduced brain serotonin levels, which was attributed to increased expression of monoamine oxidase A (MAO A). The increased MAO A expression was detected in MS WT mice at 4 weeks old and adulthood. No change in TPH2 expression was detected. To determine whether a pharmacological stressor, dexamethasone (Dex), will result in similar biochemical results obtained from MS, we used an in vitro system, SH-SY5Y cells, and found that Dex treatment resulted in increased MAO A expression levels. We then treated WT mice with Dex for 5 days, either during postnatal days 7-11 or adulthood. Both groups of Dex treated WT mice had reduced basal corticosterone and glucocorticoid receptors expression levels. However, only Dex treatment during PND7-11 resulted in reduced serotonin levels and increased MAO A expression. Just as with MS WT mice, TPH2 expression in PND7-11 Dex-treated WT mice was unaffected. Taken together, our findings suggest that both environmental and pharmacological stressors affect the expression of MAO A, and not TPH2, when applied during the critical postnatal period. This leads to long-lasting perturbations in the serotonergic system, and results in anxiety- and depressive-like behaviors.